5. Antimicrobial Activity of Balakacida (Chromolaena odorata) Endophytic Bacteria Isolated from Aceh Besar Against Staphylococcus aureus and Pseudomonas aeruginosa - Wahyu Eka Sari; Darmawi Darmawi; Morizka Wianda; Erina Erina; Rumi Sahara Zamzami; Muhammad Hambal; M. Nur Salim; Hennivanda Hennivanda; Triva Murtina Lubis (Universitas Syiah Kuala, 2020)
This study aims to isolate the balakacida (Chromolaena odorata) endophytic bacteria from Aceh Besar and to test its antimicrobial activity against pathogenic bacteria Staphylococcus aureus and Pseudomonas aeruginosa. Balakacida leaf samples were isolated and purified using nutrient agar (NA) media, followed by morphological observations and antimicrobial in vitro tests using a disk diffusion assay (Kirby Bauer). The results showed that a total of 50 endophytic bacterial colonies were isolated from the balakacida and 12 selected endophytic bacterial isolates had different morphologies from cream to yellowish cream color, then after antagonist test directly screening obtained four endophytic bacterial isolates which had the potential as antimicrobial. The results of in vitro antimicrobial tests showed that the four isolates of balakacida endophytic bacteria (BEA-1, BEA-2, BEA-3, and BEA-4) were able to inhibit the growth of pathogenic bacteria S. aureus and P. aeruginosa with the diameter of the zone of inhibition was 16.03 mm - 19.75 mm (medium inhibition category) and 15.35 mm - 21.24 mm (weak to strong inhibition category), respectively. Based on these results, it can be concluded that BEA-2 isolate has the strongest inhibition of 21.24 mm, so that it has the potential as an antimicrobial candidate for P. aeruginosa and can be used as an alternative antimicrobial product.